2021
DOI: 10.1021/acs.jnatprod.1c00083
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol Protects Human Skin Keratinocytes from Hydrogen-Peroxide-Induced Oxidative Stress via Modulation of the Caspase-1–IL-1β Axis

Abstract: Preclinical and clinical studies support cannabidiol (CBD)'s antioxidant and anti-inflammatory effects, which are linked to its skin protective effects, but there have been limited mechanistic studies reported. Herein we evaluated CBD's protective effects against hydrogen peroxide (H 2 O 2 )-induced oxidative stress in human keratinocyte HaCaT cells and explored its possible mechanism(s) of action. CBD (10 μM) protected HaCaT cells by alleviating H 2 O 2 (200 μM)-induced cytotoxicity (by 11.3%) and reactive ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 43 publications
(71 reference statements)
0
25
0
Order By: Relevance
“…Excessive generation of ROS can disrupt cellular redox homeostasis and exacerbate DNA damage, leading to cell apoptosis and inflammation [ 21 , 22 ]. Antioxidant capacity is also an important indicator for evaluating photoprotective capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive generation of ROS can disrupt cellular redox homeostasis and exacerbate DNA damage, leading to cell apoptosis and inflammation [ 21 , 22 ]. Antioxidant capacity is also an important indicator for evaluating photoprotective capacity.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, research has been conducted on the effects of cannabidiol (CBD), a phytocannabinoid found in Cannabis sativa L., which does not have psychoactive properties [5] but exhibits antioxidant and anti-inflammatory properties on the skin and skin cells [6,7]. In various experimental models, ranging from a typical in vitro experiment using cell cultures to ex vivo experiments using cells isolated from the skin of patients, and animal studies, the effects of cannabidiol have been extensively evaluated [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…ROS reduces the cell viability of keratinocytes and inhibits wound healing in OM [ 37 ]. CBD have an antiapoptotic effect on keratinocytes irradiated by ultraviolet light [ 38 , 39 ]. Considering the antiapoptotic properties of CBD, we evaluated the apoptosis of epithelial cells in mouse tongue tissue by Ki67 staining and TUNEL assay.…”
Section: Discussionmentioning
confidence: 99%